Web-based Muhammadiyah E-voting Application Using the Laravel Framework: Aplikasi E-voting Persyarikatan Muhammadiyah Berbasis Web Menggunakan Framework Laravel - Ardiansyah, Ardiansyah; Rosid, Mochamad Alfan; Fitrani, Arif Senja (Universitas Muhammadiyah Sidoarjo, 2023)
Electronic voting is a form of voting that is often used for elections using electronic systems. However, at the time of implementation there was a lot of fraud that only intended for one of the parties. Therefore, a Web-Based Muhammadiyah Association E-Voting Application was created using the Laravel Framework. There is no need to use nails because the DPT (Permanent Voters List) only needs to touch the screen to vote for the elected candidate. This application uses the RFID technology feature to start voting, so that there are no more double votes from the same voter The results of the recapitulation will periodically change according to the number of votes that have been collected and stored in the database. So it is already necessary to calculate manually when the event ends. The results of the votes are automatically counted and processed by the program quickly and efficiently.